Investigating the Lower Limit of Metallicity for the Galactic Thin Disk - Guozhen Hu; Zhengyi Shao; Erbil Gügercinoǧlu; Wenyuan Cui (The Astrophysical Journal)
We explore the metal-poor regime of the Galactic disk on the distribution of stars in the [ α /M]– V _ϕ plane, to identify the most metal-poor thin disk (MPTnD) stars belonging to the low- α sequence. Chemical abundances and velocities of sample stars are either taken or derived from APOGEE DR17 and Gaia DR3 catalogs. We find the existence of a well-separated extension of the kinematically thin disk stars in the metallicity range of −1.2 < [M/H] < −0.8 dex. Based on two-by-two distributions of [Mg/Mn], [Al/Fe] and [C+N/Fe], we further confirmed 56 high-possibility metal-poor thin disk (HP-MPTnD) giant stars and suggested the lower metallicity limit of the thin disk below −0.95 dex. A comparative analysis of the HP-MPTnD sample with other Galactic components revealed its chemo-dynamical similarities with canonical thin disk stars. These low- α metal-poor stars are predominantly located in the outer disk region and formed in the early stage of the formation of thin disk. Their existence provides compelling support for the two-infall model of the Milky Way's disk formation. Moreover, these stars impose observational constraints on the timing and metallicity of the second gas infall event.